Study of the Structural and Magnetic Properties of COFE2O4 Nanoparticles for Therapeutic Agent for Cancer Therapy (GUB Journal of Science and Engineering, 2021)
The cobalt ferrite (CoFe2O4) nanoparticles were synthesized by chemical co-precipitation technique and characterized by X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM), vibrating sample magnetometer (VSM), and Mössbauer spectroscopy. The CoFe2O4 nanoparticles coated with biocompatible chitosan at different concentrations to produce homogeneous suspensions were also characterized by dynamic light scattering (DLS) and hyperthermia set-up. XRD data of the sample explored the particle size near about 7 nm in as-dried condition. TEM micrograph of bare CoFe2O4 nanoparticles provided the particle size nearly too about 8 nm which is in good agreement with the XRD data. This particle size after coating with chitosan became 14 nm. EDX results of this sample confirmed its nano dimension with spinel structure. VSM results of the sample in as-dried condition showed the ferromagnetic character which has been beyond proved by Mössbauer spectroscopy. The hydrodynamic diameter (Hd) and polydispersity index (PDI) of the chitosan-coated samples also provided promising results. The samples were tested for their induction heating properties with an RF magnetic field of 20 mT and a frequency of 342 kHz. We also studied therapeutic efficiency in-vitro on 9L gliosarcoma cancer cells, which revealed > 98% of mortality through hyperthermia protocol with the same RF field and frequency using chitosan-coated CoFe2O4nanoparticles.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 7, Dec 2020 P 69-75